(untitled) (Biological Sciences - PJSIR, 2000)
Evaluation of 30 sweet potato (Ipomoea batatas Larn.) genotypes for yield contributing characters and tuber yield per plant revealed high phenotypic and genotypic coefficient of variation (PCY and GCY, respectively) for number of tubers per plant, average tuber weight and tuber yield per plant. The heritability and genetic advance were higher for tuber yield per plant, average tuber weight and number of tubers per plant. These three characters also reflected high heritability as well as high genetic advance. As high positive significant correlation, as well as positive direct effect of average tuber weight and number of tubers per plant on tuber yield per plant were found, these characters should be given prime importance for selecting high yielding sweet potato genotypes.